Does political discourse matter? Comparing party positions and public attitudes on immigration in England. (May 2019) - Leruth, Benjamin; Taylor-Gooby, Peter
The 2015 UK General Election campaign was mostly dominated by the issues of immigration, public debt, and income inequality. While most political parties adopted austerity-led programmes in order to reduce the level of public deficit, their stances on immigration vary significantly despite the two main parties converging on a welfare chauvinist frame. This article compares party positions to policy recommendations formulated by participants in a democratic forum as part of the 'Welfare States Futures: Our Children's Europe' project in order to determine whether recent party pledges on immigration are being used by citizens in a large group discussion over the future of welfare policy in the United Kingdom. The analysis shows that while participants are committed to tougher policies in order to reduce existing levels of net migration, most of the policy priorities formulated do not match those of the two mainstream parties (i.e. the Conservative Party and the Labour Party) but rather those of the UK Independence Party (UKIP). It also demonstrates that participants' individual political preferences do not seem to match their own positions on immigration and that there is little difference between left-leaning and right-leaning voters.